BASIC SCIENCE PROCESS SKILLS OF ELEMENTARY SCHOOL STUDENTS DURING THE CURRICULUM MERDEKA PERIOD - Isnaini Wulandari; Arrofa Acesta; Ndaru Mukti Oktaviani; Silvi Yota Fatonah (Jurnal Cakrawala Pendas, 2025)
Science process skills reflect the learning abilities and character that students must develop within themselves to prepare themselves to face a dynamic society. However, in reality, the average science process skills for elementary schools are still low and the first step before practicing and teaching science process skills in schools, teachers must know and understand the profile of students' science process skills. On the other hand, it is not yet known to what extent the science process skills of elementary school students in implementing the independent curriculum. This study aims to determine the science process skills for elementary school students in implementing the independent curriculum. This study was conducted using a case study, a qualitative research approach. The sample in this study was 12 schools spread across Kuningan Regency. The time used to carry out this study from November 2023 – January 2024. Data collection used in this study includes various methods, including observation, interviews, and documentation. The results of this study are: 1) Each subject in the independent curriculum can facilitate the development of observation skills, 2) In the independent curriculum, grouping skills are improved according to the characteristics needed in each subject, 3) Science process skills, especially the ability to measure, develop optimally in mathematics and science subjects, although other subjects still provide room to hone measuring skills.